Additive manufacturing of ni-based superalloys: effects of composition - Ghoussoub, J (2022)
Additive manufacturing (AM) is now reaching maturity as a method for processing metal alloys. It promises to bring about multifunctional component design integrating fully digital manufacturing. However, preventing cracking during processing remains a key challenge to overcome. This is of particular importance for the Ni-based superalloys used in high temperature applications such as aeronautics and power generation. In this work the effects of alloy composition on the cracking tendencies and performance of Ni-based superalloys are investigated. This study is motivated by the need to develop a better understanding of how to design new alloys specifically tailored for AM. A set of fifteen different compositions – some heritage and some novel – are studied in order to elucidate composition-microstructure-property relationships in 3D-printed Ni-based superalloys. Quantitative characterisation procedures are here developed to distinguish the two dominant cracking types that occur during AM: solidification and solid-state cracks. Experiments are carried out to explore the effects of alloy composition on the thermophyiscal, thermo-mechanical, and microstructural properties of the alloys and how these relate to the cracking phenomena observed. The magnitude of the ductility- dip (exacerbated by increasing amounts of solid solution strengthening elements) and the solidification path (widened by greater interstitial content) are unambiguously proven to be the critical factors giving rise to solid-state and solidification type cracks respectively. A model for solid-state cracking is proposed, based on an incapacity to relax the thermal stress and withstand the thermal strain arising from differential thermal contraction. This is supported by the development of novel methods for measuring the stress development during constrained cooling using electro-thermal mechanical testing. Stress relaxation by creep was found to be inconsequential during constrained bar cooling given the rapid cooling conditions of AM. This suggests that the development of highly creep resistant yet readily processable alloys is possible. The influence of the (Nb+Ta)/Al ratio is studied to tailor the properties of the novel alloys. This ratio is determined to dictate the trade-off of strength in the athermal regime, creep resistance, oxidation assisted cracking resistance, and oxidation resistance at high temperatures via alumina scale formation. The novel alloys print to γ phase and following sub-solvus heat treatment (with no solutionizing step) generate desirable γ/γ′ microstructures tied to good properties. Further assessment of the high temperature oxidation behaviour of all fifteen alloys provides alloy design guidelines for developing oxidation-resistant alloys for AM. In summary, this work highlights the potential to develop new alloys specifically for AM with properties matching those of the heritage ones designed for investment casting.